(3GdfGehS GdCYXe hGdbGehS GdCbOe aj eYQaI bOQ GdfHi Udi Gddg Ydjg hSdes - (3YHO GdcQje Hf EHQGgje GdcjdGfjs
(3ChdgG (B:s
(3CeG HYO aEfi SCdJ hGQO GdJMbjb GdeDjO HGdYUeI hGdJhajb Yf SQ GdCdhgjI hMbjbI GdQHhHjI hGdYHhOjI s
(3BNQgG (B:s
(3dCfg YQa QHg eYQaJg dfaSg hdjcf gPG BNQ GdcJGH hGddg Gdehab ddUhGH hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3cJGH GdfhQ GdeJecf ai eYfi bhdg GdeDef eQBI GdeDefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1922s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(202) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs